How Is Academic Culture Influenced by Internationalization? - Benitez, Milena (International Higher Education, 2019)
Internationalization processes have an impact on higher education systems and institutions. The mechanisms of these processes—rankings, cooperation, academic mobility, and curriculum reforms—influence teaching and learning, research, and service practice. In turn, academic culture is also impacted: the institutions’ own sets of beliefs, norms, habits, and values. Internationalization processes generate new challenges, tensions, and conflicts, and allow higher education institutions to reevaluate institutional strategies in a global context.